2016
DOI: 10.2903/j.efsa.2016.4567
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on an application by Syngenta (EFSA‐GMO‐DE‐2011‐99) for the placing on the market of maize Bt11 × 59122 × MIR604 × 1507 × GA21 and twenty subcombinations, which have not been authorised previously independently of their origin, for food and feed uses, import and processing under Regulation (EC) No 1829/2003

Abstract: In this opinion, the EFSA GMO Panel assesses the five-event stack maize and 20 of its subcombinations independently of their origin. The EFSA GMO Panel has previously assessed the five single events that are combined to produce this five-event stack maize Bt11 9 59122 9 MIR604 9 1507 9 GA21 and did not identify safety concerns. No new data on the single events, leading to a modification of the original conclusions on their safety, were identified. The molecular, agronomic, phenotypic and compositional data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Taking into account the previous assessment and the new information, the GMO Panel concludes that maize 5307, as assessed in the scientific opinion on application EFSA- GMO-DE-2011-95 (EFSA GMO Panel, 2015 and in the supplementary toxicity study, is as safe and nutritious as its conventional counterpart in the scope of the application. Background and Terms of Reference as provided by the requestor On 16 April 2015, the GMO Panel adopted a scientific opinion on application EFSA-GMO-DE-2011-95 for the placing on the market of maize 5307 for food and feed uses, import and processing under Regulation (EC) No 1829/2003(EFSA GMO Panel, 2015. In this scientific opinion, the GMO Panel considered that the information available for maize 5307 was not sufficient to reach a final overall conclusion since 'the EFSA GMO Panel cannot conclude on the safety of the eCry3.1Ab protein'.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the previous assessment and the new information, the GMO Panel concludes that maize 5307, as assessed in the scientific opinion on application EFSA- GMO-DE-2011-95 (EFSA GMO Panel, 2015 and in the supplementary toxicity study, is as safe and nutritious as its conventional counterpart in the scope of the application. Background and Terms of Reference as provided by the requestor On 16 April 2015, the GMO Panel adopted a scientific opinion on application EFSA-GMO-DE-2011-95 for the placing on the market of maize 5307 for food and feed uses, import and processing under Regulation (EC) No 1829/2003(EFSA GMO Panel, 2015. In this scientific opinion, the GMO Panel considered that the information available for maize 5307 was not sufficient to reach a final overall conclusion since 'the EFSA GMO Panel cannot conclude on the safety of the eCry3.1Ab protein'.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data provided, it can be concluded that the sequence differences found in maize event DAS-59122-7 in 2016 were already present in the original material used in the risk assessment process (EFSA, 2007(EFSA, , 2008(EFSA, , 2009aEFSA GMO Panel, 2010a, 2013, 2016. Furthermore, the differences identified are located outside the coding sequences of the newly expressed proteins Cry34Ab1, Cry35Ab1 and PAT; two nucleotides are in the TA peroxidase promoter of the cry35Ab1 expression cassette and one nucleotide is in the 5 0 genomic flanking region.…”
Section: Assessmentmentioning
confidence: 97%